The global crisis and the future of the dollar: Toward Bretton Woods III? - Jörg Bibow (Levy Economics Institute of Bard College, 2010)
This paper investigates the United States dollar's role as the international currency of choice as a key contributing factor in critical global developments that led to the crisis of 2007-09, and considers the future role of the dollar as the global economy emerges from that crisis. It is argued that the dollar is likely to retain its hegemonic status for a few more decades, but that United States spending powered by public rather than private debt would provide a more sustainable motor for global growth. In the process, the 'Bretton Woods II' regime depicted by Dooley, Folkerts-Landau, and Garber (2003) as sustainable despite featuring persistent U.S. current account deficits may turn into a 'Bretton Woods III' regime that sees U.S. fiscal policy and public debt as 'minding the store' in maintaining U.S. and global growth.
Keywords: E12; E61; E62; F02; F33; 330; reserve currency; global monetary order; global financial crisis